Unlocking Digital Literacy in Indonesia: Insights from the Use of Social Media Platforms - Ratri, Safitri Yosita; Aviyanti, Lina (Jurnal Prima Edukasia, 2025)
The use of social media platforms has become increasingly integrated into students' everyday lives as technology advances, particularly with the rise of remote learning and digital connectivity. Despite these rapid adoptions, digital literacy challenges remain, including finding, evaluating, utilising, sharing, and creating content responsibly. This study examines how social media platforms shape students' minds and underscore the importance of digital literacy skills as a result of their experiences and perceptions of these platforms. Using a qualitative research approach, the study conducted a systematic review of data collected from students in Indonesia. The data were then analyzed and integrated to identify patterns, trends, and common themes across the literature. The analysis revealed several themes, including popular features of social media, learning advantages, the role of adults, and the importance of safe social media use. The findings highlight the critical role of digital literacy in enabling students to navigate social media platforms effectively. This study provides valuable insights for educators, policymakers, and parents on adopting and implementing social media platforms while fostering appropriate digital literacy skills among students.